Analisis Repurchase Intention Produk Skincare Lokal melalui Live Commerce TikTok dengan Customer Satisfaction sebagai Variabel Intervening - Fajriah, Niftira; Sarma, Mamun (IPB University, 2025)
The development of the internet has brought significant changes to business activities, leading to the emergence of e-commerce. E-commerce continues to evolve and innovate, resulting in live commerce platforms, one of which is TikTok. The rising popularity of TikTok live commerce has caused a shift in consumer behavior, particularly in the skincare industry. This also creates new challenges for skincare businesses to achieve customer satisfaction and encourage repurchase intention. This study aims to understand the characteristics of TikTok users and how live streaming and promotions affect repurchase intention, with customer satisfaction as an intervening variable. This quantitative research obtained primary data from questionnaires distributed to 130 respondents in the Jabodetabek area and analyzed using the SEM-PLS method. The results show that live streaming and promotions have a positive and significant impact on repurchase intention through customer satisfaction as an intervening variable.